P-OGC87 Robotic Techniques in Esophagogastric Cancer Surgery: An Assessment of Short- and Long-term Clinical Outcomes. (16th December 2021) - Kamarajah, Sivesh; Griffiths, Ewen; Phillips, Alexander; Ruurda, Jelle; van Hillegersberg, Richard; Hofstetter, Wayne; Markar, Sheraz
Abstract: Background: Robotic esophagogastric cancer surgery is gaining widespread adoption. This population-based cohort study aimed to compare rates of textbook outcomes (TO) and survival from robotic minimally invasive techniques for esophagogastric cancers. Methods: Data from the United States National Cancer Database (NCDB) (2010-2017), was used to identify patients with non-metastatic esophageal and gastric cancers receiving open (esophagus, n = 11, 442; stomach, n = 22, 183), laparoscopic (esophagus (LAMIE), n = 4, 827; stomach (LAMIG), n = 6, 359) or robotic (esophagus (RAMIE), n = 1, 657; stomach (RAMIG), n = 1, 718) surgery. TO were defined as lymph nodes examined >15, margin-negative resections, length of stay <21 days, no 30-day readmission, and no 90-day mortality. Multivariable logistic regression and Cox analyses were used to account for treatment selection bias. Results: Patients receiving robotic surgery were more commonly treated within high volume, academic centers and with advanced clinical T and N stage disease. From 2010 to 2017, TO rates increased for esophageal and gastric cancer treated by all surgical techniques. RAMIE (odds ratio (OR):1.41, (CI 95% : 1.27-1.58) and RAMIG (OR:1.30, CI 95% : 1.17-1.45) had significantly higher TO rates compared to open surgery. For esophagectomy, TO (hazard ratio (HR):0.64, CI 95% : 0.60-0.67) and RAMIE (HR:0.92, CI 95% : 0.84-1.00) were both associated with long-term survival. For gastrectomy, TO (HR:0.58, CI 95% : 0.56-0.60) and both LAMIG (HR:0.89, CI 95% : 0.85-0.94) and RAMIG (HR:0.88, CI 95% : 0.81-0.96) were all associated with long-term survival. Subset analysis in high volume centers confirmed similar findings. Conclusions: Despite potentially adverse learning curve effects and more advanced tumor stages captured within the study period, both RAMIE and RAMIG, as performed in mostly high-volume centers, were associated with improved TO and long-term survival. Therefore, consideration for wider adoption but a well-designed phase III RCT is required to fully evaluate the benefits of robotic techniques in esophageal and gastric cancers.